PROGRAM BUDGETING AS A TOOL OF MUNICIPAL FINANCE MANAGEMENT - M. V. Galazova (Вестник университета, 2020)
The article has been devoted to the analysis of features of application of program budgeting in municipalities, and also to identification of problems at its application. One of the important conditions for maintaining stable socio-economic development of the municipality is the effective management of municipal finances. The system of management of municipal finances should be aimed at their effective use in the framework of budget policy objectives. Software budgeting can be a modern tool for effective management of municipal finances. The structure of the expenditure part of the budgets of municipalities of the Republic of North Ossetia – Alania in the framework of program activities and non-program activities has been analyzed in the paper. Methods of increasing the effectiveness of program budgeting have been proposed.